Occurrence and distribution of microplastics in an urban river: A case study in the Pearl River along Guangzhou City, China - Lin, Lang; Zuo, Lin-Zi; Peng, Jin-Ping; Cai, Li-Qi; Fok, Lincoln; Yan, Yan; Li, Heng-Xiang; Xu, Xiang-Rong (The Science of the total environment, 2018)
Microplastics, as emerging contaminants in the global environment, have become a cause for concern for both academics and the public. The present understanding of microplastic pollution is primarily focused on marine environments, and less attention has been given to freshwater environments, in particular, to urban rivers. In this study, microplastics were sampled from surface water and sediments in 14 sites located in the lower course of the Pearl River. These sampling sites are located along Guangzhou of South China, with built-up areas being the dominant land use. The abundances of microplastics in surface water and sediments ranged from 379 to 7924 items·m−3 and 80 to 9597 items·kg−1, respectively. Polyethylene and polypropylene were the common types of microplastics, together accounting for 64.3% and 73.8% of surface water and sediment samples, respectively. Fibers were the dominant microplastic shapes in both water and sediment samples. The abundances of microplastics varied in surface water and sediments with each site, which might be affected by multiple factors. Our results indicated that wastewater treatment plants (WWTP) could reduce microplastics from municipal sewage which was finally discharged into the Pearl River along Guangzhou. [Display omitted] •Microplastics in the Pearl River along Guangzhou were investigated for the first time.•Fibers were detected in both surface water and sediment samples.•PE and PP were the dominant polymer types in surface water and sediments.•WWTP in Guangzhou could reduce microplastic pollution in the municipal sewage.